India, bharat and Pakistan: the Constitutional journey of a sandwiched civilisation - J Sai Deepak; DEEPAK (J Sai) (New Delhi Bloomsbury, 2022)
India, Bharat and Pakistan, the second book of the Bharat Trilogy, takes the discussion forward from its bestselling predecessor, India That Is Bharat. It explores the combined influence of European and Middle Eastern colonialities on Bharat as the successor state to the Indic civilisation, and on the origins of the Indian Constitution. To this end, the book traces the thought continuum of Middle Eastern coloniality from the rise of Islamic Revivalism in the 1740s following the decline of the Mughal Empire, which presaged the idea of Pakistan, until the end of the Khilafat Movement in 1924, which cemented the road to Pakistan. The book also describes the collaboration of convenience that was forged between the proponents of Middle Eastern coloniality and the British colonial establishment to the detriment of the Indic civilisation. One of the objectives of this book is to help the reader draw parallels between the challenges faced by the Indic civilisation in the tumultuous period from 1740 to 1924, and the present day. Its larger goal remains the same as that of the first, which is to enthuse Bharatiyas to undertake a critical decolonial study of Bharat$1 (Bs history, especially in the context of the Constitution, so that the religiosity towards the document is moderated by a sense of proportion, perspective and purposes
Keywords: Seeds of Pakistan; Aligarh Movement; Partition of Bengal; Khilafat